Expression of macrophage inflammatory protein-3 beta/CCL19 in pulmonary sarcoidosis - Gibejova, Agata; Mrazek, Frantisek; Subrtova, Daniela; Sekerova, Veronika; Szotkowska, Jaroslava; Kolek, Vitezslav; du Bois, Roland M; Petrek, Martin (American journal of respiratory and critical care medicine, 2003)
In this study, messenger RNA (mRNA) expression for novel T lymphocyte chemoattractants, leukotactin-1, macrophage inflammatory protein (MIP)-3 alpha and MIP-3 beta was investigated in bronchoalveolar lavage fluid (BALF) cells from patients with sarcoidosis, a T cell-mediated disease with typical CD4+ lymphocyte alveolitis. Of these three chemokines, only MIP-3 beta mRNA was upregulated in sarcoidosis, and therefore, protein levels of this chemokine, its pharmacologic regulation, and association with disease clinical course were explored. MIP-3 beta protein concentrations were elevated in BALF from sarcoid patients compared with control subjects (p = 0.001) and in patients with chest X-ray stage II chemokine protein levels were increased compared with stage I (p = 0.003). MIP-3 beta protein was associated predominantly with alveolar macrophages and correlated with BALF lymphocytes and T cell subsets. mRNA expression for the MIP-3 beta receptor, CC chemokine receptor 7, was increased in sarcoidosis and correlated with MIP-3 beta protein levels. MIP-3 beta mRNA and protein expression in BALF cells was suppressed by dexamethasone and cyclosporine A in vitro. In conclusion, MIP-3 beta is implicated in T lymphocyte recruitment in sarcoidosis, is associated with disease progression, and is downregulated by drugs used for sarcoidosis treatment. This novel chemokine, therefore, represents a candidate for studies of sarcoidosis pathobiologic mechanisms.
Keywords: Female; cyklosporin; receptory chemokinů; lidé středního věku; Severity of Illness Index; Receptors, CCR6; Sarcoidosis, Pulmonary; progrese nemoci; imunohistochemie; dexamethason; plicní sarkoidóza; Dexamethasone; Lymphocyte Activation; Macrophages, Alveolar; mužské pohlaví; polymerázová řetězová reakce s reverzní transkripcí; receptory CCR6; Case-Control Studies; exprese genu; Humans; Chemokine CCL19; dospělí; alveolární makrofágy; stupeň závažnosti nemoci; Immunohistochemistry; chemokin CCL20; Macrophage Inflammatory Proteins; lidé; down regulace; Middle Aged; Reverse Transcriptase Polymerase Chain Reaction; chemokin CCL19; Down-Regulation; Bronchoalveolar Lavage Fluid; Chemokines, CC; makrofágové zánětlivé proteiny; RNA, Messenger; senioři; bronchoalveolární lavážní tekutina; aktivace lymfocytů; T-lymfocyty; Chemokine CCL20; messenger RNA; ženské pohlaví; studie případů a kontrol; Gene Expression; Disease Progression; Aged; T-Lymphocytes; Receptors, Chemokine; Adult; chemokiny CC; Male; Cyclosporine